Positive electrode material, preparation method thereof and lithium ion battery

By acid-treating iron oxide and performing gradient temperature calcination, the polarization problem of lithium iron phosphate material during high current charge and discharge is solved, its electrochemical performance and cycle performance are improved, a regular, uniformly sized crystal structure is formed, and particle agglomeration is reduced.

CN120622445APending Publication Date: 2025-09-12GUANGDONG BRUNP RECYCLING TECH CO LTD +3

Patent Information

Application Number
CN202510818721.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-18
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

In the prior art, the intrinsic conductivity of lithium iron phosphate material is poor, resulting in severe polarization during high current charging and discharging. The prior art is difficult to solve the technical problem.

Method used

By acid-treating the iron oxide, impurities and loose oxide layers on its surface are removed, exposing more active sites. The acid treatment and calcination are carried out by gradient temperature increase to form a regular, uniformly sized crystal structure, reduce particle agglomeration, and improve particle dispersion and gradation.

Benefits of technology

The reaction activity and particle dispersibility of iron oxide are significantly improved, forming an excellent positive electrode material and improving the electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622445A_ABST
    Figure CN120622445A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a preparation method thereof and a lithium ion battery, and belongs to the technical field of battery materials. Comprising the following steps: carrying out acid treatment on ferric oxide to obtain acid-modified ferric oxide; and mixing the acid-modified iron oxide, a second iron source, a lithium source and a phosphorus source to obtain a mixture, and then roasting the mixture to obtain the positive electrode material. By performing acid treatment on the ferric oxide, on one hand, impurities and a loose oxide layer on the surface of the ferric oxide can be removed, more active sites can be exposed, the reactivity of the ferric oxide is matched with that of the second iron source, the reaction process is carried out synergistically, and formation of a regular and uniform-size crystal structure is promoted; a foundation is laid for obtaining a positive electrode material with excellent electrochemical performance; on the other hand, the surfaces of the iron oxide particles can be regulated and controlled, so that agglomeration among the particles can be reduced when the iron oxide particles are mixed with the second iron source particles, the dispersity of the particles is improved, and the mixture forms more excellent gradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium iron phosphate (LiFePO4) material, as the positive electrode material of lithium-ion batteries, has become the mainstream choice for power batteries and energy storage systems due to its high safety, long cycle life, low cost and environmental friendliness.

[0003] However, the intrinsic conductivity of lithium iron phosphate material is poor, which leads to severe polarization during large current charging and discharging, limiting its rate performance; insufficient capacity performance restricts the improvement of energy density; the capacity decays rapidly in the later stage of the cycle, and the lifespan still needs to be optimized.

[0004] To this end, researchers have conducted extensive research in material structure, preparation process, and interface regulation. For example, carbon coating is introduced to improve the conductivity of lithium iron phosphate materials and inhibit particle agglomeration. However, uneven or excessive thickness of the carbon coating layer will increase the interfacial impedance, resulting in an increase in polarization voltage at high rates. Nanoparticles are prepared by sol-gel or solvothermal methods to shorten the lithium ion diffusion path and increase the electrolyte contact area. However, nanoparticles are prone to agglomeration during the cycle, resulting in a decrease in the utilization rate of active substances. Spray drying is used to prepare secondary particle structures to improve the capacity performance of lithium iron phosphate materials. Although the secondary particle structure can alleviate the early capacity loss, the capacity retention rate still decreases with the increase in the number of cycles due to lithium dendrite growth and interface side reactions in the later stage of the cycle, especially under high temperature (>45°C) conditions. In addition, the particle size distribution of this process varies significantly between batches, which easily leads to an increase in the dispersion of battery performance, which is not conducive to industrial production.

[0005] Therefore, how to further optimize the structure of lithium iron phosphate materials and improve their electrochemical performance is a technical problem that needs to be solved urgently. Summary of the Invention

[0006] In view of the deficiencies in the prior art, the present invention aims to provide a positive electrode material, a preparation method thereof, and a lithium-ion battery. The present invention achieves surface modification of iron oxide by acid treatment of iron oxide. On the one hand, it can remove impurities and loose oxide layers on the surface of iron oxide, expose more active sites, significantly improve the reactivity of iron oxide, match the reactivity of iron oxide with that of the second iron source, achieve synergistic reaction, promote the formation of a regular, uniformly sized crystal structure, and lay the foundation for obtaining a positive electrode material with excellent electrochemical performance; on the other hand, it can also regulate the surface of iron oxide particles. The surface charge distribution of acid-modified iron oxide particles is more uniform, which can reduce the agglomeration phenomenon between particles when mixed with the second iron source particles, improve the dispersibility of particles, and form a more excellent particle gradation of the mixture. The positive electrode material prepared based on this preparation method has excellent electrochemical performance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a positive electrode material, the preparation method comprising the following steps:

[0009] The iron oxide is treated with acid to obtain acid-modified iron oxide.

[0010] The acid-modified iron oxide, the second iron source, the lithium source and the phosphorus source are mixed to obtain a mixture, and then the mixture is calcined to obtain the positive electrode material.

[0011] The present invention achieves surface modification of iron oxide by acid treatment of iron oxide. On the one hand, it can remove impurities and loose oxide layers on the surface of iron oxide, expose more active sites, significantly improve the reactivity of iron oxide, match the reactivity of iron oxide with the second iron source, achieve synergistic reaction process, promote the formation of regular, uniformly sized crystal structures, and lay the foundation for obtaining positive electrode materials with excellent electrochemical performance. On the other hand, it can also regulate the surface of iron oxide particles. The surface charge distribution of acid-modified iron oxide particles is more uniform. When mixed with the second iron source particles, it can reduce the agglomeration phenomenon between particles, improve the dispersibility of particles, and form a more excellent particle gradation of the mixture. The positive electrode material prepared based on this preparation method has excellent electrochemical performance.

[0012] The present invention changes the surface properties of the iron oxide by subjecting the iron oxide to acid treatment, thereby making it easier to refine the iron oxide during the mixing process.

[0013] It should be noted that if the iron oxide is not treated with acid, the untreated iron oxide will have low activity due to the presence of surface impurities and oxide layers, and it will be difficult to fully play its role in the crystal growth reaction process. Its participation will be low, which will easily lead to an increase in crystal structure defects and affect the electrochemical properties of the positive electrode material. The surface properties of the iron oxide particles are uneven, and they are prone to agglomeration with the second iron source particles, resulting in unreasonable particle grading and difficulty in achieving the ideal grading effect. The reaction process of the untreated iron oxide and the second iron source is not synchronized (for example, iron phosphate over-reacts while the iron oxide reaction is incomplete), which can easily produce side reactions or uneven composition problems, affecting the electrochemical properties of the positive electrode material.

[0014] Preferably, during the acid treatment, the acid solution used includes inorganic acid and / or organic acid.

[0015] Preferably, the inorganic acid includes any one or a combination of at least two of phosphoric acid, nitric acid, hydrochloric acid and sulfuric acid.

[0016] Preferably, the organic acid comprises any one or a combination of at least two of oxalic acid, citric acid, malic acid, tartaric acid and acetic acid.

[0017] Preferably, the concentration of the acid solution is 0.05-0.5 mol / L, for example, it can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L or 0.5 mol / L, etc.

[0018] In the present invention, the appropriate concentration of the acid solution is conducive to dissolving the surface oxide layer of the iron oxide while maintaining its nanoparticle structure, inhibiting the dissolution of the matrix iron, and only reacting on the surface without destroying the structure of the iron oxide itself.

[0019] Preferably, the solid-liquid ratio of the iron oxide to the acid solution is 1 g:(2-4) mL, for example, 1 g:2 mL, 1 g:3 mL or 1 g:4 mL.

[0020] The present invention adopts a suitable solid-liquid ratio, which helps to efficiently remove the surface oxide layer while ensuring the structural integrity of the iron oxide particles, achieve surface activation and efficient impurity removal, and avoid excessive dissolution of the matrix structure, providing an ideal precursor for subsequent lithium iron phosphate synthesis.

[0021] It should be noted that the solid-liquid ratio refers to the ratio of the mass of iron oxide to the volume of the acid solution.

[0022] Preferably, the acid treatment is a staged acid treatment, which includes a first stage and a second stage performed sequentially, and the temperature of the first stage is lower than the temperature of the second stage.

[0023] In the present invention, the staged acid treatment is performed in a gradient temperature increase manner, which helps to balance the efficiency of oxide layer dissolution and the protection of the iron oxide particle structure, and avoids the explosive dissolution caused by a single-stage high-temperature treatment.

[0024] Preferably, the acid solution used in the first stage is of the same type as or different from the acid solution used in the second stage.

[0025] Preferably, the temperature of the first stage is 30-60°C, for example, 30°C, 40°C, 50°C or 60°C, and the insulation time is 3-7h, for example, 3h, 4h, 5h, 6h or 7h.

[0026] Preferably, the temperature of the second stage is 50-80°C, such as 50°C, 60°C, 70°C or 80°C, and the holding time is 0.5-3h, such as 0.5h, 1h, 2h or 3h.

[0027] Preferably, the heating rate in the first stage is 0.2-0.6°C / min, for example, 0.2°C / min, 0.3°C / min, 0.4°C / min, 0.5°C / min or 0.6°C / min.

[0028] Preferably, the heating rate in the second stage is 0.2-0.6°C / min, for example, 0.2°C / min, 0.3°C / min, 0.4°C / min, 0.5°C / min or 0.6°C / min.

[0029] Preferably, the D50 of the acid-modified iron oxide is 0.1-1.5 μm, for example, 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.1 μm, 1.3 μm or 1.5 μm.

[0030] It should be noted that the D50 of acid-modified iron oxide refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. The same applies to the following.

[0031] Preferably, the second iron source includes any one of ferrous oxalate, ferric phosphate dihydrate and anhydrous ferric phosphate, or a combination of at least two thereof.

[0032] Preferably, D50 of the second iron source is 2-15 μm, for example, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm or 15 μm.

[0033] Preferably, the molar ratio of the iron element in the acid-modified iron oxide to the iron element in the second iron source is (0.05-0.5):1, for example, it can be 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1 or 0.5:1.

[0034] In the present invention, the acid-modified iron oxide and the second iron source in a suitable molar ratio cooperate with each other to better exert a synergistic effect, fill the pores between the particles, optimize the packing density of the particles, and achieve a more excellent polarization effect.

[0035] Preferably, the lithium source includes any one or a combination of at least two of lithium carbonate, lithium hydroxide, lithium acetate, lithium acetate, lithium citrate and lithium dihydrogen phosphate.

[0036] Preferably, the phosphorus source includes any one or a combination of at least two of ammonium dihydrogen phosphate, anhydrous ferric phosphate, dihydrate ferric phosphate, phosphoric acid and lithium dihydrogen phosphate.

[0037] Preferably, the molar ratio of Fe:Li:P in the mixture is 1:(1-1.07):(1.01-1.05), wherein the selection range of Li "1-1.07" can be, for example, 1, 1.01, 1.02, 1.03, 1.04 or 1.05, etc., and the selection range of P "1.01-1.05" can be, for example, 1.01, 1.02, 1.03, 1.04 or 1.05, etc.

[0038] Preferably, the mixing process is accompanied by grinding.

[0039] Preferably, the grinding method includes ball milling or sand milling.

[0040] Preferably, the grinding rate is 500-1200 rpm, for example, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm or 1200 rpm.

[0041] Preferably, the D50 of the mixture is 0.35-0.85 μm, for example, it can be 0.35 μm, 0.45 μm, 0.55 μm, 0.65 μm, 0.75 μm or 0.85 μm.

[0042] Preferably, the roasting treatment includes primary roasting and secondary roasting, and the temperature of the primary roasting is lower than the temperature of the secondary roasting.

[0043] The present invention adopts a multi-stage calcination method with gradient temperature increase for calcination treatment, which helps to form a "dense crystal core-porous carbon shell" structure in the positive electrode material particles, avoiding problems such as uneven carbon coating and LiFePO4 lattice defects caused by the large temperature span in traditional single-stage calcination.

[0044] Preferably, the primary calcination temperature is 300-700°C, for example, 300°C, 400°C, 500°C, 600°C or 700°C, and the holding time is 4-9h, for example, 4h, 5h, 6h, 7h, 8h or 9h.

[0045] Preferably, the temperature of the secondary calcination is 650-850°C, for example, 650°C, 700°C, 750°C, 800°C or 850°C, and the holding time is 8-20h, for example, 8h, 10h, 12h, 14h, 16h, 18h or 20h.

[0046] Preferably, the calcination treatment is carried out in an inert atmosphere, for example, nitrogen or argon.

[0047] In a second aspect, the present invention provides a positive electrode material, which is prepared using the preparation method described in the first aspect.

[0048] In a third aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery includes the positive electrode material as described in the second aspect.

[0049] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) The present invention achieves surface modification of iron oxide by subjecting iron oxide to acid treatment. On the one hand, it can remove impurities and loose oxide layers on the surface of iron oxide, expose more active sites, and significantly improve the reaction activity of iron oxide, so that the reaction activity of iron oxide matches that of the second iron source, realize the coordinated progress of the reaction process, promote the formation of a regular and uniformly sized crystal structure, and lay the foundation for obtaining positive electrode materials with excellent electrochemical properties. On the other hand, it can also regulate the surface properties of iron oxide particles. The surface charge distribution of acid-modified iron oxide particles is more uniform. When mixed with the second iron source particles, it can reduce the agglomeration phenomenon between particles, improve the dispersibility of particles, and make the mixture form a better particle grading.

[0052] (2) The positive electrode material prepared based on this preparation method has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a process flow chart provided for Example 1 of the present invention. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1

[0056] This embodiment provides a method for preparing a positive electrode material, and its process flow chart is as follows: Figure 1 As shown, the preparation method comprises the following steps:

[0057] (1) Iron oxide with a D50 of 0.9 μm was mixed with an acid solution and heated to 45°C at a heating rate of 0.3°C / min for the first stage of acid treatment. Then, the temperature was raised to 65°C at a heating rate of 0.3°C / min for the second stage of acid treatment to obtain acid-modified iron oxide with a D50 of 0.88 μm.

[0058] The acid solution is a phosphoric acid solution with a concentration of 0.15 mol / L; the solid-liquid ratio of iron oxide to acid solution is 1 g:3 mL.

[0059] (2) The acid-modified iron oxide, the second iron source, the lithium source, and the phosphorus source are ball-milled to obtain a mixture having a D50 of 0.45 μm.

[0060] Among them, the second iron source is ferric phosphate dihydrate with a D50 of 4.31 μm, the lithium source is lithium carbonate, and the phosphorus source is ammonium dihydrogen phosphate; the molar ratio of iron in the acid-modified iron oxide to the iron in the second iron source is 0.15:1; the molar ratio of Fe:Li:P in the mixture is 1:1.03:1.04; and the ball milling mixing speed is 1000 rpm.

[0061] (3) Under a nitrogen atmosphere, the mixture is subjected to primary calcination and secondary calcination in sequence, and after the calcination, the mixture is cooled, washed and dried to obtain the positive electrode material.

[0062] Among them, the temperature of the first roasting is 400℃, and the holding time is 6h; the temperature of the second roasting is 800℃, and the holding time is 10h.

[0063] Example 2

[0064] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:

[0065] (1) Iron oxide with a D50 of 1.2 μm was mixed with an acid solution and heated to 30°C at a heating rate of 0.3°C / min for the first stage of acid treatment. Then, the temperature was raised to 50°C at a heating rate of 0.3°C / min for the second stage of acid treatment to obtain acid-modified iron oxide with a D50 of 1.15 μm.

[0066] The acid solution is a nitric acid solution with a concentration of 0.3 mol / L; the solid-liquid ratio of iron oxide to acid solution is 1 g:2 mL.

[0067] (2) The acid-modified iron oxide, the second iron source, the lithium source, and the phosphorus source are ball-milled to obtain a mixture having a D50 of 0.4 μm.

[0068] Among them, the second iron source is ferric phosphate dihydrate with a D50 of 5.58 μm, the lithium source is lithium carbonate, the phosphorus source is ammonium dihydrogen phosphate, the molar ratio of iron in the acid-modified iron oxide to the iron in the second iron source is 0.5:1, the molar ratio of Fe:Li:P in the mixture is 1:1.03:1.04, and the ball milling mixing speed is 500 rpm.

[0069] (3) Under a nitrogen atmosphere, the mixture is subjected to primary calcination and secondary calcination in sequence, and after the calcination, the mixture is cooled, washed and dried to obtain the positive electrode material.

[0070] The temperature of the first calcination is 300°C and the holding time is 9 hours; the temperature of the second calcination is 750°C and the holding time is 20 hours.

[0071] Example 3

[0072] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:

[0073] (1) Iron oxide with a D50 of 1.2 μm was mixed with an acid solution and heated to 60°C at a heating rate of 0.5°C / min for the first stage of acid treatment. Then, the temperature was raised to 80°C at a heating rate of 0.5°C / min for the second stage of acid treatment to obtain acid-modified iron oxide with a D50 of 1 μm.

[0074] The acid solution is oxalic acid solution with a concentration of 0.5 mol / L; the solid-liquid ratio of iron oxide to acid solution is 1 g:4 mL.

[0075] (2) The acid-modified iron oxide, the second iron source, the lithium source, and the phosphorus source are ball-milled to obtain a mixture having a D50 of 0.38 μm.

[0076] Among them, the second iron source is ferrous oxalate with a D50 of 3.2 μm, the lithium source is lithium carbonate; the phosphorus source is ammonium dihydrogen phosphate; the molar ratio of iron in the acid-modified iron oxide to the iron in the second iron source is 0.25:1; the molar ratio of Fe:Li:P in the mixture is 1:1.05:1.03; and the ball milling mixing speed is 1200 rpm.

[0077] (3) Under a nitrogen atmosphere, the mixture is subjected to primary calcination and secondary calcination in sequence, and after the calcination, the mixture is cooled, washed and dried to obtain the positive electrode material.

[0078] The temperature of the first roasting is 350°C and the holding time is 8 hours; the temperature of the second roasting is 830°C and the holding time is 8 hours.

[0079] Example 4

[0080] The difference between this embodiment and embodiment 1 is that after the first stage of acid treatment, filtration and washing are performed, and then the washed iron oxide is placed in a sulfuric acid solution with a concentration of 0.15 mol / L and heated to 65°C at a heating rate of 0.3°C / min for the second stage of acid treatment.

[0081] The rest of the preparation methods and parameters remained the same as in Example 1.

[0082] Example 5

[0083] The difference between this embodiment and embodiment 1 is that the concentration of the acid solution in step (1) is 0.01 mol / L.

[0084] The rest of the preparation methods and parameters remained the same as in Example 1.

[0085] Example 6

[0086] The difference between this embodiment and embodiment 1 is that the concentration of the acid solution in step (1) is 1.5 mol / L.

[0087] The rest of the preparation methods and parameters remained the same as in Example 1.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 1 is that the solid-to-liquid ratio of the iron oxide and the acid solution in step (1) is 1 g:6 mL.

[0090] The rest of the preparation methods and parameters remained the same as in Example 1.

[0091] Example 8

[0092] The difference between this embodiment and embodiment 1 is that the solid-to-liquid ratio of the iron oxide and the acid solution in step (1) is 1 g:1 mL.

[0093] The rest of the preparation methods and parameters remained the same as in Example 1.

[0094] Example 9

[0095] The difference between this embodiment and embodiment 1 is that the first stage of acid treatment is not performed.

[0096] The rest of the preparation methods and parameters remained the same as in Example 1.

[0097] Example 10

[0098] The difference between this embodiment and embodiment 1 is that the second stage of acid treatment is not performed.

[0099] The rest of the preparation methods and parameters remained the same as in Example 1.

[0100] Example 11

[0101] The difference between this embodiment and embodiment 1 is that the temperature of the first stage acid treatment is 80°C.

[0102] The rest of the preparation methods and parameters remained the same as in Example 1.

[0103] Example 12

[0104] The difference between this embodiment and embodiment 1 is that the temperature of the second stage acid treatment is 30°C.

[0105] The rest of the preparation methods and parameters remained the same as in Example 1.

[0106] Example 13

[0107] The difference between this embodiment and embodiment 1 is that the molar ratio of the iron element in the acid-modified iron oxide and the iron element in the second iron source in step (2) is 0.02:1.

[0108] The rest of the preparation methods and parameters remained the same as in Example 1.

[0109] Example 14

[0110] The difference between this embodiment and embodiment 1 is that the molar ratio of the iron element in the acid-modified iron oxide and the iron element in the second iron source in step (2) is 0.6:1.

[0111] The rest of the preparation methods and parameters remained the same as in Example 1.

[0112] Comparative Example 1

[0113] The difference between this comparative example and Example 1 is that step (1) is not performed, that is, the un-acid-modified iron oxide, the second iron source, the lithium source and the phosphorus source are directly ball-milled and mixed.

[0114] The rest of the preparation methods and parameters remained the same as in Example 1.

[0115] Comparative Example 2

[0116] The difference between this comparative example and Example 1 is that the second iron source is not added in step (2).

[0117] The rest of the preparation methods and parameters remained the same as in Example 1.

[0118] Performance Testing

[0119] The lithium-ion battery is prepared based on the positive electrode materials provided in the above embodiments and comparative examples, and the specific steps include:

[0120] The above-mentioned positive electrode material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1 and added to N-methylpyrrolidone solvent to obtain a positive electrode slurry, which is then coated on aluminum foil and dried to obtain a positive electrode plate; artificial graphite is used as the negative electrode plate; the electrolyte is a 1 mol / L lithium hexafluorophosphate solution (the solvent includes ethylene carbonate, dimethyl carbonate and diethyl carbonate in a volume ratio of 1:1:1), and the separator is a polyethylene separator; the above-mentioned positive electrode plate, negative electrode plate and separator are assembled, and then the electrolyte is injected to obtain a CR2032 button battery.

[0121] The capacity performance and cycle performance tests of the above-mentioned CR2032 button battery are carried out under the following test conditions: the initial discharge capacity is tested at room temperature of 25°C, the charge and discharge voltage is 2.0-3.75V, and the initial charge and discharge rate is 0.1C; the cycle performance is tested at room temperature of 25°C, the charge and discharge voltage is 2.0-3.75V, and the charge and discharge rate is 1C for 200 cycles.

[0122] The 5C rate performance test was carried out under the following conditions: at room temperature of 25°C, the charge and discharge voltage was 2.0-3.75V, and the discharge specific capacity was measured at a charge and discharge rate of 5C.

[0123] The test results are shown in Table 1.

[0124] Table 1

[0125]

[0126]

[0127] analyze:

[0128] As shown in Table 1, the present invention realizes surface modification of iron oxide by acid treatment of iron oxide. On the one hand, impurities and loose oxide layer on the surface of iron oxide can be removed, exposing more active sites, significantly improving the reactivity of iron oxide, making iron oxide match the reactivity of the second iron source, realizing the coordinated progress of the reaction process, promoting the formation of a regular, uniformly sized crystal structure, and laying the foundation for obtaining a positive electrode material with excellent electrochemical performance. On the other hand, the surface properties of iron oxide particles can be regulated, and the surface charge distribution of acid-modified iron oxide particles is more uniform. When mixed with the second iron source particles, the agglomeration phenomenon between particles can be reduced, the dispersibility of particles is improved, and the mixture is formed into a more excellent particle gradation. The positive electrode material prepared based on this preparation method has excellent electrochemical performance.

[0129] It can be seen from Examples 1 and 4 that the acid treatment in the first stage and the acid treatment in the second stage use different acid solutions in synergistic cooperation, which is beneficial to dissolving the oxide layer and impurities on the surface of the iron oxide while regulating the surface roughness, enhancing the chemical bonding with the second iron source, thereby enabling a more sufficient chemical reaction with the lithium source, phosphorus source, etc., laying the foundation for the subsequent acquisition of a positive electrode material with a better grading effect.

[0130] By comparing Example 1 with Examples 5-6, it can be seen that if the concentration of the acid solution is too low, the surface oxide layer is not completely dissolved, impurities remain, the active sites are insufficiently exposed, and it is impossible to fully cooperate with the second carbon source, resulting in poor electrical performance of the positive electrode material; if the concentration of the acid solution is too high, excessive dissolution is likely to occur, the yield is extremely low, and the process requirements cannot be met.

[0131] By comparing Example 1 with Examples 7-8, it can be seen that if the solid-liquid ratio of iron oxide and acid solution is too small, although it does not affect the dissolution of its oxide layer and impurities, and the electrical properties do not deteriorate significantly, the excessive amount used increases the cost, which is not conducive to cost reduction and efficiency improvement; if the solid-liquid ratio of iron oxide and acid solution is too large, the wetting uniformity of the acid solution and iron oxide is poor, the surface etching is uneven, and the unmodified area has poor reaction activity during the sintering process, which affects the performance of the lithium iron phosphate battery.

[0132] By comparing Example 1 with Examples 9-10, it can be seen that if the first stage of acid treatment is not carried out, the untreated oxide layer needs to be dissolved in the second stage of acid treatment, and the iron oxide cannot be fully activated, resulting in poor electrical properties of the synthesized lithium iron phosphate positive electrode material; if the second stage of acid treatment is not carried out, only part of the oxide layer and impurities are dissolved, and the iron oxide is not fully activated, which affects the electrical properties of the material.

[0133] By comparing Example 1 with Examples 11-12, it can be seen that if the temperature of the acid treatment in the first stage is too high, excessive dissolution will occur, which will not only dissolve the surface oxide layer and impurities, but also dissolve the particle structure of the iron oxide, affecting the yield of the acid-modified iron oxide; if the temperature of the acid treatment in the second stage is too low, the iron oxide cannot be fully activated, affecting the electrical performance.

[0134] By comparing Example 1 with Examples 13-14, it can be seen that if the molar ratio of the iron element in the acid-modified iron oxide to the iron element in the second iron source is too small, the filling synergistic effect is insufficient, which affects the electrical properties of the material; if the molar ratio of the iron element in the acid-modified iron oxide to the iron element in the second iron source is too large, there are too many small particles, the material bulk density is low, and the energy density of the material is affected.

[0135] By comparing Example 1 with Comparative Example 1, it can be seen that if step (1) is not performed, that is, the unacid-modified iron oxide, the second iron source, the lithium source and the phosphorus source are directly ball-milled and mixed, the untreated iron oxide has low activity due to the presence of surface impurities and an oxide layer, and is difficult to fully play its role in the reaction process of crystal growth. The participation is low, which easily leads to an increase in crystal structure defects and affects the electrochemical properties of the positive electrode material; the surface properties of the iron oxide particles are uneven, and they are easy to agglomerate with the second iron source particles, resulting in unreasonable particle grading and difficulty in achieving an ideal grading effect; the reaction process of the untreated iron oxide and the second iron source is not synchronized (for example, the iron phosphate over-reacts and the iron oxide reaction is incomplete), which easily produces side reactions or uneven composition problems, affecting the electrochemical properties of the positive electrode material.

[0136] From the comparison between Example 1 and Comparative Example 2, it can be seen that if the second iron source is not added in step (2) to cooperate with the acid-modified iron oxide, although the 0.1C discharge does not deteriorate significantly, the discharge performance at high rate deteriorates, indicating that the removal of the second iron source is not conducive to the improvement of rate performance.

[0137] It should be noted that while the present invention illustrates the process method through the above-described embodiments, the present invention is not limited to the above-described process steps, and does not necessarily rely on the above-described process steps for implementation. Those skilled in the art will appreciate that any improvements to the present invention, equivalent replacements for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The preparation method comprises the following steps: treating the iron oxide with acid to obtain acid-modified iron oxide; The acid-modified iron oxide, the second iron source, the lithium source and the phosphorus source are mixed to obtain a mixture, and then the mixture is calcined to obtain the positive electrode material.

2. The preparation method according to claim 1, characterized in that During the acid treatment, the acid solution used includes inorganic acid and / or organic acid; Preferably, the inorganic acid comprises any one or a combination of at least two of phosphoric acid, nitric acid, hydrochloric acid and sulfuric acid; Preferably, the organic acid comprises any one or a combination of at least two of oxalic acid, citric acid, malic acid, tartaric acid and acetic acid; Preferably, the concentration of the acid solution is 0.05-0.5 mol / L; Preferably, the solid-liquid ratio of the iron oxide to the acid solution is 1 g:(2-4) mL.

3. The preparation method according to claim 1 or 2, characterized in that The acid treatment is a staged acid treatment, which includes a first stage and a second stage performed sequentially, wherein the temperature of the first stage is lower than the temperature of the second stage; Preferably, the acid solution used in the first stage is of the same type as or different from the acid solution used in the second stage.

4. The preparation method according to claim 3, characterized in that The temperature of the first stage is 30-60°C and the holding time is 3-7h; Preferably, the temperature of the second stage is 50-80°C and the holding time is 0.5-3h; Preferably, the heating rate in the first stage is 0.2-0.6°C / min; Preferably, the heating rate in the second stage is 0.2-0.6°C / min.

5. The preparation method according to any one of claims 1 to 4, characterized in that The D50 of the acid-modified iron oxide is 0.1-1.5 μm; Preferably, the second iron source comprises any one or a combination of two of ferrous oxalate, ferric phosphate dihydrate and anhydrous ferric phosphate; Preferably, the D50 of the second iron source is 2-15 μm.

6. The preparation method according to any one of claims 1 to 5, characterized in that The molar ratio of the iron element in the acid-modified iron oxide to the iron element in the second iron source is (0.05-0.5):1; Preferably, the lithium source includes any one or a combination of at least two of lithium carbonate, lithium hydroxide, lithium acetate, lithium acetate, lithium citrate and lithium dihydrogen phosphate; Preferably, the phosphorus source includes any one or a combination of at least two of ammonium dihydrogen phosphate, anhydrous ferric phosphate, dihydrate ferric phosphate, phosphoric acid and lithium dihydrogen phosphate; Preferably, the molar ratio of Fe:Li:P in the mixture is 1:(1-1.07):(1.01-1.05).

7. The preparation method according to any one of claims 1 to 6, characterized in that The mixing process is accompanied by grinding; Preferably, the grinding method includes ball milling or sand milling; Preferably, the grinding rate is 500-1200 rpm; Preferably, the D50 of the mixture is 0.35-0.85 μm.

8. The preparation method according to claim 1, characterized in that The roasting treatment includes primary roasting and secondary roasting, and the temperature of the primary roasting is lower than the temperature of the secondary roasting; Preferably, the primary calcination temperature is 300-700°C, and the holding time is 4-9h; Preferably, the temperature of the secondary calcination is 650-850°C, and the holding time is 8-20h; Preferably, the atmosphere of the calcination treatment is an inert atmosphere.

9. A positive electrode material, characterized in that The positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The positive electrode sheet of the lithium-ion battery includes the positive electrode material as claimed in claim 9.

Citation Information

Patent Citations

  • Method for preparing carbon-coated lithium iron phosphate from modified ferric oxide

    CN105633404A

  • Method for one-step solid-phase synthesis of lithium iron phosphate based on ferric oxide

    CN117819506A

  • Method for Preparing Lithium Iron Phosphate as a Positive Electrode Active Material for a Lithium Ion Secondary Battery

    US20100102270A1

Cited By

  • Iron phosphate and preparation method thereof, graded iron phosphate and lithium iron phosphate positive electrode material

    CN121672448A